Beyond Mechanization : Work and Technology in a Postindustrial Age - Benedict, Daniel (Relations Industrielles / Industrial Relations, 1985)
This article reviews the book, "Beyond Mechanization : Work and Technology in a Postindustrial Age," by Larry Hirschhorn.